Use of recombinant cytokines for optimized induction of antiviral immunity against SIV in the nonhuman primate model of human AIDS - Ansari, Aftab A. (Immunol Res, 2004)
Outbreaks of infectious diseases such as HIV and the much televised and attention-getting outbreaks of diseases such as Ebola, Hantaviruses, and the most recent outbreak of SARS have induced a significant new interest in the formulations and more importantly the science of vaccinology, which has previously to a large extent been conducted empirically. Our laboratory has focused on the use of recombinant nonhuman primate cytokines as adjunctive therapies for inducing antigen-specific immune responses in monkeys because most recombinant human cytokines appear to be immunogenic. This article provides a summary of our work with such cytokines, which includes attempts to define optimum dosing schedules that lead to optimal primary and lasting memory antigen-specific immune responses.